Correlation between Level of Serum Transaminases and Duration of Antiepileptic Drugs in Epilepsy Children in Sanglah Hospital - Suwarba, I Gusti Ngurah Made; Santhi, Anak Agung Ratna Purnama; Mahalini, Dewi Sutriani (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Some antiepileptic drugs (AEDs), particularly sodium valproate, phenytoin, phenobarbital, and carbamazepine induce and increase production of hepatic enzymes. The adverse metabolic effects of AEDs treatments have become main concern, however data about evaluation of serum transaminases and duration of AEDs in Indonesia still limited. AIM: The aim of the study was to investigate correlation of AEDs and serum transaminases in children with epilepsy. METHODS: This cross-sectional research was conducted in pediatric neurology outpatient clinic in Sanglah Hospital. The target was children with epilepsy who had taken AEDs for at least 6 months. Data were collected from January 2020 to the number of samples were achieved. The exclusion criteria were concomitant liver disease, taking drugs which induce elevated serum transaminase or alcohol abuse. Data including age, gender, nutritional status, type, and duration of AEDs were obtained from medical record. Correlation was analyzed by Pearson’s or Spearman’s correlation, p < 0.05 was considered significant. RESULTS: Total 148 epileptic children enrolled in this study. Aspartate transaminase (AST) and alanine aminotransferase (ALT) level were highest in the group receiving combination therapy (34.37 ± 24.9 U/L and 35.96 ± 23.3 U/L). There was a significant negative correlation between duration of carbamazepine and AST (r = –0.723, p = 0.0001) and ALT (r = –0.457, p = 0.009), as well as duration of valproic acid with AST and ALT (r = –0.689 and –0.677, p = 0.0001). Duration of phenobarbital administration was positively correlated with AST and ALT (r = 0.546 and 0.425, p = 0.0001). Combination therapy also had positive correlation with AST and ALT (r = 0.815 and 0.781, p = 0.0001, respectively). CONCLUSION: Duration administration of carbamazepine and valproic acid had negative correlation with AST and ALT; however, phenobarbital and combination therapy were positively correlated with AST and ALT.